The comER Gene Plays an Important Role in Biofilm Formation and Sporulation in both Bacillus subtilis and Bacillus cereus - Yan, Fang; Yu, Yiyang; Wang, Luyao; Luo, Yuming; Guo, Jian-hua; Chai, Yunrong (Frontiers in Microbiology, 2016)
Bacteria adopt alternative cell fates during development. In Bacillus subtilis, the transition from planktonic growth to biofilm formation and sporulation is controlled by a complex regulatory circuit, in which the most important event is activation of Spo0A, a transcription factor and a master regulator for genes involved in both biofilm formation and sporulation. In B. cereus, the regulatory pathway controlling biofilm formation and cell differentiation is much less clear. In this study, we show that a novel gene, comER, plays a significant role in biofilm formation as well as sporulation in both B. subtilis and B. cereus. Mutations in the comER gene result in defects in biofilm formation and a delay in spore formation in the two Bacillus species. Our evidence supports the idea that comER may be part of the regulatory circuit that controls Spo0A activation. comER likely acts upstream of sda, a gene encoding a small checkpoint protein for both sporulation and biofilm formation, by blocking the phosphor-relay and thereby Spo0A activation. In summary, our studies outlined a conserved, positive role for comER, a gene whose function was previously uncharacterized, in the regulation of biofilm formation and sporulation in the two Bacillus species.